Excessive folic acid intake combined with undernutrition during gestation alters offspring behavior and brain monoamine profiles. (17th May 2022) - Ono, Tetsuo; Hino, Kodai; Kimura, Tomoko; Uchimura, Yasuhiro; Ashihara, Takashi; Higa, Takako; Kojima, Hideto; Murakami, Takashi; Udagawa, Jun
Abstract: Dietary folic acid augmentation during gestation reduces neurodevelopmental disorder risk in offspring; however, it is still unclear if excessive maternal folic acid intake can impair brain function in offspring. We examined if excessive folic acid intake throughout gestation altered the behavior of male offspring under poor nutrition during early gestation (E5.5–E11.5). Dams were divided into four groups: control (CON, 2 mg folic acid/kg of food), excessive folic acid fortification (FF, 10 mg folic acid/kg of food), undernutrition (UN, 40% food reduction from E5.5–E11.5), and excessive folic acid fortification plus undernutrition (UN‐FF). Excess maternal folic acid fortification induced hyperactivity in the open‐field and lower anxiety‐like behavior in the elevated plus maze at 9 weeks of age. These behavioral changes were accompanied by reduced dopamine in the prefrontal cortex (PFC), norepinephrine in the amygdala, and 5‐hydroxytryptamine (5‐HT) in the dorsal midbrain (DM), PFC, and amygdala where 5‐HT neurons project from the DM. Furthermore, canonical discriminant analysis, including dopamine and DOPAC concentrations in the PFC, norepinephrine concentrations in the PFC, amygdala, and pons, and 5‐HT and 5‐HIAA concentrations in the amygdala and DM, correctly classified 73.5% of the offspring in CON, FF, UN, and UN‐FF groups. The first discriminant function mainly classified groups based on nutritional status, whereas the second function mainly classified groups based on folic acid intake. Our study suggests that combined transformations of brain monoamine profiles by maternal undernutrition and excess folic acid intake is involved in the behavioral alteration of offsprings.